How older adults and their informal carers prevent falls: An integrative review of the literature. (June 2018) - Wilkinson, Amanda; Meikle, Nicole; Law, Phoebe; Yong, Hui Jia; Butler, Philip; Kim, Justin; Mulligan, Hilda; Hale, Leigh
Abstract: Falls in older persons are prevalent and costly for the individual and the health system. Falls prevention guidelines have been developed from best evidence to minimise falls in older persons. Aim: To synthesise the literature on falls prevention strategies used by community dwelling older persons and/or their informal carers and to compare the commonly adopted strategies with those recommended by falls prevention guidelines. Data sources: Health sciences databases for full text articles published in English plus reference list searching of included articles. Review method: An integrative review approach. Studies were included if they identified fall prevention management strategies used by community dwelling older adults and/or their informal carers. Quality appraisal was undertaken using appropriate Joanna Briggs Institute critical appraisal tools. Information relevant to the aim of the review were extracted and coded into categories then inductively sorted into sub-themes and themes. Results: Of the seventeen studies included in the review, eleven identified older adults' falls prevention strategies, two investigated fall prevention strategies used by carers, and four explored perspectives of older persons together with their carers, representing the perspectives of an estimated 501 older persons and 102 carers. Strategies used by older adults arose because of self-awareness about their changing physical ability, and advice and support mainly from family or friends. Carer fall prevention strategy was predominantly around protection of the older adult from falling by discouraging independence. Conclusions: The fall self-management strategies adopted by older adults and their carers to prevent falls, in the main, do not align with international best practice fall prevention guidelines.